Development of Functional Antibodies Directed to Human Dialyzable Leukocyte Extract (Transferon®). (16th May 2019) - Mellado-Sánchez, Gabriela; Lázaro-Rodríguez, Juan José; Avila, Sandra; Vallejo-Castillo, Luis; Vázquez-Leyva, Said; Carballo-Uicab, Gregorio; Velasco-Velázquez, Marco; Medina-Rivero, Emilio; Pavón, Lenin; Chacón-Salinas, Rommel; Pérez-Tapia, Sonia Mayra
Abstract : Transferon® is an immunomodulator made of a complex mixture of peptides from human dialyzable leucocyte extracts (hDLEs). Development of surrogate antibodies directed to hDLE is an indispensable tool for studies during process control and preclinical trials. These antibodies are fundamental for different analytical approaches, such as identity test and drug quantitation, as well as to characterize its pharmacokinetic and mechanisms of action. A previous murine study showed the inability of the peptides of Transferon® to induce antibody production by themselves; therefore, in this work, two approaches were tested to increase its immunogenicity: chemical conjugation of the peptides of Transferon® to carrier proteins and the use of a rabbit model. Bioconjugates were generated with Keyhole Limpet Hemocyanin (KLH) or Bovine Serum Albumin (BSA) through maleimide-activated carrier proteins. BALB/c mice and New Zealand rabbits were immunized with Transferon® conjugated to KLH or nonconjugated Transferon®. Animals that were immunized with conjugated Transferon® showed significant production of antibodies as evinced by the recognition of Transferon®-BSA conjugate in ELISA assays. Moreover, rabbits showed higher antibody titers when compared with mice. Neither mouse nor rabbits developed antibodies when immunized with nonconjugated Transferon®. Interestingly, rabbit antibodies were able to partially block IL-2 production in Jurkat cells after costimulation with Transferon®. In conclusion, it is feasible to elicit specific and functional antibodies anti-hDLE with different potential uses during the life cycle of the product.